Diabetes in South and Central America: An update - Aschner, Pablo (2013)
The estimated population of the South and Central America (SACA) Region is 467.6 million and 64% is in the age range of 20–79 years but the population pyramid and age distribution are changing. The average prevalence of diabetes in the Region is 8.0% and is expected to reach 9.8% by the year 2035. Prevalence is much lower in rural settings than in urban and the differences attributed to lifestyle changes may be a target for intervention. The indigenous population is a particularly vulnerable group needing special attention. On average, 24% of the adult cases with diabetes are undiagnosed but in some countries this is still as high as 50%. Health expenditure due to diabetes in the Region is around 9% of the global total. Inadequate glycemic control, defined as HbA1c >7%, is a strong predictor of chronic complications which increase resource use in the Region and less than half of the patients enrolled in diabetes care programmes are at target. Fifty percent or more of the adult population is overweight/obese and around one third of the adult population has metabolic syndrome using regional cutoffs for waist circumference. The number of people with IGT is almost equal to those with diabetes presenting an additional challenge for prevention. Children with type 1 diabetes represent only 0.2% of the total population with diabetes but the incidence may be increasing. In many places they have limited access to insulin, and even when available, it is not used appropriately. The available epidemiological data provide the background to act in developing national diabetes programmes which integrate diabetes care with cardiovascular prevention and promote diabetes prevention as well.